Psychosocial Review On Substance Use Among Youth Transgender In Penang, Malaysia - Kumarashwaran Vadevelu; Azlinda Azman; Paramjit Singh Jamir Singh (2024)
This qualitative study was conducted in Penang, Malaysia with the aim to analyze and gather indepth understanding of challengers faced by youth Transgender who engaged with substance drug used. This study also aims to understand some of the psychosocial support received by this marginal population in term of overcoming their substance use behaviour. Selection of 18 respondents was through the snowballing sampling technique due to the difficulty of getting the targeted respondents. Respondents who have participated in this study were among transgender populations between the ages of 18-40. The study findings indicated that almost all the respondents have never taken drugs in their life but only 4 respondents who have experienced taking cannabis and methamphetamine ecstasy or over a period of 12 months ago. This study suggests that both government and non-governmental organizations (NGOs) should continue to provide appropriate HIV and AIDS intervention among the transgender population. Social work intervention primarily in educating this marginal population towards the prevention of HIV transmission especially preventing from drugs substance uses which are associated with behaviors that facilitate HIV transmission in their daily life.